Prediction of Potential Habitat Distributions and Climate Change Impacts on the Rare Species Woonyoungia septentrionalis (Magnoliaceae) in China Based on MaxEnt - Weihao Yao; Zenghui Wang; Yu Fan; Danyang Liu; Zeyang Ding; Yumei Zhou; Shuyue Hu; Wei Zhang; Jing Ou (Plants)
Changes in species’ habitats provide important insights into the effects of climate change. Woonyoungia septentrionalis, a critically endangered species endemic to karst ecosystems, has a highly restricted distribution and is a key biological resource. Despite its ecological importance, the factors influencing its habitat suitability and distribution remain poorly understood. This study employed ecological niche modeling to predict the potential distribution of Woonyoungia septentrionalis across China and analyzed shifts in centroid location to explore migration pathways under current and future climate scenarios. The model exhibited high predictive accuracy (AUC = 0.988), indicating its robustness in assessing habitat suitability. Under current climatic conditions, Woonyoungia septentrionalis is predominantly found in the Guizhou–Guangxi border region, southeastern Yunnan, eastern Sichuan, southeastern Tibet, and parts of Chongqing, Hunan, and Hubei. Among these, the Guizhou-Guangxi border represents the primary suitable habitat. Temperature factors, particularly bio6 (minimum temperature of the coldest month) and bio7 (annual temperature range), were the most significant determinants of habitat suitability, contributing 43.29% and 12.65%, respectively. Soil cation exchange capacity (CEC) accounted for 15.82%, while precipitation had a relatively minor impact. Under future climate scenarios, suitable habitats for Woonyoungia septentrionalis are projected to shrink and shift toward higher altitudes and latitudes, increasing the risk of extinction due to the “mountain trap” effect, where migration is constrained by limited habitat at higher elevations. Stable habitats, particularly in Libo (Guizhou) and Huanjiang (Guangxi), are identified as critical refugia. We recommend prioritizing shrinking and stable habitats in Guizhou, Guangxi, and Yunnan for in situ conservation. Ex situ conservation efforts should focus on areas identified based on key environmental factors and predicted migration pathways to ensure the species’ long-term survival. This study provides both theoretical and practical guidance for the conservation of this species and its vulnerable habitat.